Influence of Iron-Filings on Marshall and Volumetric Properties of Asphalt Concrete - Al-Tuwayyij, Husham; Sarsam, Saad Issa (Salehan Institute of Higher Education, 2020)
The growth and expansion of road infrastructure had resulted in the continuous use of materials, increased construction costs of flexible pavements and increased environmental impact during the service life of the road. Consequently, many researchers have sought to use methods to maintain these roadways sustain environmental impact and traffic loads. One of these approaches is the use of additives to improve asphalt's volumetric character. In this research, iron filings were used as partial replacement of fine aggregates, and the Marshall and volumetric properties were assessed before and after the implementation of iron filings. Specimens were prepared with iron filings addition of (2, 4, 6 and 8%) by weight of fine aggregates. The Marshall mix design procedure was used to calculate the optimum asphalt content and the volumetric properties, including bulk density, Total voids, voids in mineral aggregates V.M.A., and voids filled with asphalt V.F.A. The Marshall Flow and Stability were calculated. Test results were assessed before and after the inclusion of the iron filings. It was concluded that the addition of iron filings can enhance the Marshall and volumetric properties of asphalt. The stability increased by 15% when replacing fine aggregates by 2%, of iron filings by total weight. Also, the air voids and the VMA decreased by increasing the percentage of iron filings, while VFA was not significantly affected as compared to the conventional specimen. The ideal ratio of iron filings which fulfill the optimal requirements was 5%.